2003
DOI: 10.1080/0142159031000136743
|View full text |Cite
|
Sign up to set email alerts
|

The Supplemental Instruction Project: peer-devised and delivered tutorials

Abstract: The purpose of this study was to determine whether student devised and delivered supplemental instruction is beneficial and acceptable to first-year medical students. A student-run Supplemental Instruction Project (SIP) was developed and delivered by second-year medical students and offered free of charge to all first-year medical students at Memorial University of Newfoundland taking the Integrated Study of Disease I course in 1999 and again in 2000. Small-group tutorials focused on subject material that seco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
32
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(33 citation statements)
references
References 7 publications
1
32
0
Order By: Relevance
“…Eight studies found that the academic performance of students who received peer tutoring was better, 16,[20][21][22][23][24][25]27 1 study found mixed results, 31 and 1 found the performance of peer-tutored students to be lower. 35 Ten studies compared the academic performance of students who received peer tutoring to that of students who received faculty tutoring.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Eight studies found that the academic performance of students who received peer tutoring was better, 16,[20][21][22][23][24][25]27 1 study found mixed results, 31 and 1 found the performance of peer-tutored students to be lower. 35 Ten studies compared the academic performance of students who received peer tutoring to that of students who received faculty tutoring.…”
Section: Resultsmentioning
confidence: 99%
“…15 Participation in 9 of these peer tutoring programs was voluntary. 21,22,24,25,27,30,31,34,35 Voluntary participation and the exclusion of students who likely had the lowest academic ability possibly affected study outcomes and limits the generalizability of the findings of these studies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…PAL is useful to academic institutions, since it offers opportunities to reduce faculty teaching load and fills gaps in the curriculum [6][7][8] . It also helps students develop communication and professional skills and provide support to each other with less stress compared to that felt in the presence of experts [7,9] .…”
Section: Introductionmentioning
confidence: 99%
“…Teaching activities are led by the departmental academic staff and the students are the passive recipients. Tutorial classes [2] are also conducted by the departmental academic staff. Tutorial is an interactive session where students express their opinions, ask questions and enhance their communication skills during tutorials.…”
Section: Introductionmentioning
confidence: 99%